2013
DOI: 10.1080/09613218.2013.757886
|View full text |Cite
|
Sign up to set email alerts
|

Summertime temperatures and thermal comfort in UK homes

Abstract: [213 words]Internal summertime temperatures measured in 268 homes in the UK city of Leicester are reported. The hourly data was collected from living rooms and bedrooms during the summer of 2009, which was generally cool but with a short hot spell. Some household interviews were conducted. The sample of homes is statistically representative of the socio-technical characteristics of the city's housing stock. The data provides insight into the influence of house construction, energy system usage and occupant cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 19 publications
(14 reference statements)
10
86
1
1
Order By: Relevance
“…In concert with the storage capacity of modern laptops and easy-to-use statistical software, these campaigns have exposed the scale and extent of the overheating problem and have started to shed a light on which people, in which homes in which locations are most at risk. The reviews in the papers in this issue provide this background literature, but the following works are particularly notable (Armstrong et al, 2011;Beizaee, Lomas, & Firth, 2013;Lomas & Kane, 2013;Mavrogianni, Wilkinson, Davies, Biddulph, & Oikonomou, 2012, and associated works; Mavrogianni, Taylor, Davies, Thoua, & Kolm-Murray, (Palmer, Godoy-Shimizu, Tillson, & Manditt, 2016). i BUS -Building Use Studies questionnaire (e.g., Leaman, Stevenson, & Bordass, 2010).…”
Section: Why Is Overheating a Problem And Why Now?mentioning
confidence: 99%
“…In concert with the storage capacity of modern laptops and easy-to-use statistical software, these campaigns have exposed the scale and extent of the overheating problem and have started to shed a light on which people, in which homes in which locations are most at risk. The reviews in the papers in this issue provide this background literature, but the following works are particularly notable (Armstrong et al, 2011;Beizaee, Lomas, & Firth, 2013;Lomas & Kane, 2013;Mavrogianni, Wilkinson, Davies, Biddulph, & Oikonomou, 2012, and associated works; Mavrogianni, Taylor, Davies, Thoua, & Kolm-Murray, (Palmer, Godoy-Shimizu, Tillson, & Manditt, 2016). i BUS -Building Use Studies questionnaire (e.g., Leaman, Stevenson, & Bordass, 2010).…”
Section: Why Is Overheating a Problem And Why Now?mentioning
confidence: 99%
“…The overheating risk in UK apartments has been identified by previous studies as particularly high, compared to other dwelling types (Beizaee et al, 2013;Lomas and Kane, 2013). In the mild UK climate, where the external summer temperature relatively rarely rises above a comfortable internal temperature, the vulnerability of apartments is due to their relatively low external surface to floor area ratio compared to detached houses.…”
Section: Introductionmentioning
confidence: 96%
“…CIBSE static overheating criteria for bedrooms relates to occupied hours only and these are typically assumed to be between 23:00-7:00, however it is worth noting that four out of the 95 BUS survey respondents and one of the 21 indepth study households worked in shifts which meant that their sleeping hours did not match those considered in the earlier studies (Lomas and Kane, 2013). Prevailing occupancy patterns for the 18 households were established based on repeated home visits and interview findings.…”
Section: Monitored Temperaturesmentioning
confidence: 99%
“…The urban heat island highly affects indoor comfort conditions in low-income housing. Studies performed in different parts of the world have shown indoor comfort conditions during heat waves exceeded highly the set threshold limits for health and wellbeing [24][25][26]. It is characteristic that maximum indoor temperatures in low-income houses in Athens, Greece during the 2007 heat wave have reached 45 °C, while long spells with indoor temperatures above 30 °C are recorded [25].…”
Section: Direct and Indirect Costs And Consequences Of The "Negative mentioning
confidence: 99%